2008
DOI: 10.1164/rccm.200802-359oc
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Ventilation Alters Mesenchymal Cell Turnover and Improves Alveolarization in Preterm Lambs

Abstract: Rationale: Bronchopulmonary dysplasia (BPD) is a frequent cause of morbidity in preterm infants that is characterized by prolonged need for ventilatory support in an intensive care environment. BPD is characterized histopathologically by persistently thick, cellular distal airspace walls. In normally developing lungs, by comparison, remodeling of the immature parenchymal architecture is characterized by thinning of the future alveolar walls, a process predicated on cell loss through apoptosis. Objectives: We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 66 publications
3
87
1
Order By: Relevance
“…The data presented previously and in this report indicate that HAB-CPAP provides considerable ventilation, either through nasal prong interfaces or through endotracheal tubes. The failure of HAB-CPAP0 and HAB-CPAP90 to ventilate the paralyzed rabbits in our studies is also consistent with previous reports of others (7,8) who observed limited or insufficient ventilation using standard B-CPAP. The additional gas movement provided by the higher amplitude pressure fluctuations caused by the action at the bubbler air-water interface of the HAB-CPAP135 seems to be pivotal to the capabilities of this device.…”
Section: Discussionsupporting
confidence: 93%
“…The data presented previously and in this report indicate that HAB-CPAP provides considerable ventilation, either through nasal prong interfaces or through endotracheal tubes. The failure of HAB-CPAP0 and HAB-CPAP90 to ventilate the paralyzed rabbits in our studies is also consistent with previous reports of others (7,8) who observed limited or insufficient ventilation using standard B-CPAP. The additional gas movement provided by the higher amplitude pressure fluctuations caused by the action at the bubbler air-water interface of the HAB-CPAP135 seems to be pivotal to the capabilities of this device.…”
Section: Discussionsupporting
confidence: 93%
“…Another difference, at least during the initial years using the preterm lamb model, is that the ductus arteriosus was surgically ligated within a few days of preterm birth (6,20,139). The protocol was subsequently changed to let the ductus close spontaneously (5,135,150). Rationale for eliminating ductal ligation was to minimize surgical trauma to the lung and postoperative edema, inflammation, infection, and atelectasis.…”
Section: Animal Models As Tools To Identify Pathogenic Mechanisms Leamentioning
confidence: 99%
“…Both models also recapitulate the pathophysiology and pathology of evolving neonatal CLD in preterm baboons (46,49,50,58,63,124,199) and preterm lambs (5,6,20,24,25,111,139,150). We use the term "evolving neonatal CLD" for the preterm baboon and preterm lamb models and reserve the term "BPD" for preterm human infants, to avoid confusion between large-animal models vs. the human disease.…”
Section: Animal Models As Tools To Identify Pathogenic Mechanisms Leamentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulated apoptosis may contribute to the structural aberrations associated with acute and chronic lung diseases, including BPD (36)(37)(38). On the other hand, enhanced apoptosis of mesenchymal cells has been associated with improved alveolarization and thinning of airspace walls (51). At PN7, apoptosis was enhanced in the alveolar septa of IL-1b/b6 2/2 mice compared with IL-1b/b6 1/1 mice.…”
Section: Apoptosis and Proliferation In The Lungsmentioning
confidence: 99%